The Identical External Reference Point Standardized to the Zero-Reference Level for Measuring Both Central and Jugular Venous Pressures: An Observational Study - Niraj Karmacharya; Madhur Dev Bhattarai; Amita Pradhan (Critical Care Research and Practice)
Background. Studies report discrepancies between CVP and JVP measurements. The mid-thoracic plane (MTP) at the anterior fourth intercostal space level indicates the zero-reference level (ZRL) for venous pressure measurement, and the midaxillary line (MAL) at fourth intercostal space is a point near the ZRL in the supine position. JVP is usually measured from the sternal angle (SA) with further addition of 5 cm (JVP-SA + 5) and CVP in the supine position from MAL (CVP-MAL). However, no report has compared CVP measured from MTP (CVP-MTP) with CVP-MAL and with JVP from MTP (JVP-MTP) and JVP-SA + 5. Methods. We measured JVP-MTP and JVP-SA + 5 in appropriate reclining positions and subsequently CVP-MTP and CVP-MAL in the supine position blindly in 150 patients. We compared the pressures by Pearson correlation and Bland–Altman plots. Results. CVP-MTP and CVP-MAL demonstrated similar means (p=0.129), strong positive linear relationship (r = 0.908), and good agreement (near-zero mean difference) with each other. JVP-MTP was about 1 cm higher than JVP-SA + 5 (p<0.001). JVP-MTP displayed higher correlation coefficients and better agreements with both CVPs than JVP-SA+5. Correlation coefficients and mean differences of both CVPs with JVP-MTP were almost equal, about 0.83 and 1 cm, and with JVP-SA + 5 also almost equal, about 0.72 and 2 cm, respectively. Conclusions. JVP tallies better with CVP examined in the supine position when both are measured from MTP as the identical external reference point (ERP), and MAL can be used as MTP to measure CVP in the supine position. Our findings indicate the way to explore the matching of CVP and JVP to the full extent possible by standardizing their measurements from other identical ERPs to that from the zero-reference level MTP. Their further study in similar higher reclining positions from identical ERPs, such as MTP, MAL, and SA with the addition of higher numbers instead of 5 cm, is warranted standardizing other measurements to that from MTP.